Empowering manufacturing personnel through functional understanding. Issue 8 (11th June 2018) - Michalakoudis, Ioannis; Aurisicchio, Marco; Childs, Peter; Koutlidis, Apollon; Harding, James
Abstract: A growing interest in knowledge management and standardisation, has increasingly led organisations to implement employee training programs. For the manufacturing workforce, however, these remain limited to informal 'On-the-Job' approaches, administered by peer colleagues – particularly in Small and Medium Enterprises (SMEs) where economic, educational, cognitive and cultural constraints are often deeply embedded. This paper proposes a methodology for training the manufacturing workforce on the functions of products, and presents a case study conducted in a UK-based manufacturing SME – aiming to verify our two research hypotheses: a) Functional Analysis Diagrams of the company's products and parts would assist in knowledge assimilation; and, b) knowledge assimilation has a positive effect on work quality and productivity levels. By applying statistical inference methods on long-term quantitative data and survey results, we confirmed substantial improvements in work quality (63%) and increased productivity (67%), supporting our hypotheses and suggesting that the proposed methodology can be a promising solution for the industry.